Examining ACTV: An argument for implementing neuroscience-based and trauma- informed treatment models in offender treatment programs. (May 2019) - Schauss, Eraina; Zettler, Haley R.; Russell, Amanda
Abstract: There is a well-established link between experiencing traumatic events in childhood such as witnessing violence and later perpetration of domestic violence. Within the United States, literature in the area of domestic violence has largely neglected the link between the neuroscience of trauma exposure in childhood and later instances of perpetration. Few research studies have explored the neurological impact of adverse childhood experiences on adult offending behavior. Additionally, the most common treatment models for these offenders do not focus on addressing prior trauma that may be related to offending behavior. Through the development of two theoretical models, this paper explores the relationship between childhood trauma and later perpetration of domestic violence. This paper argues that ACTV (Achieving Change Through Values-Based Behavior), a relatively new treatment model that incorporates elements of mindfulness, interoception, and experiential avoidance may be an effective treatment intervention for domestic violence offenders with a history of trauma. Highlights: Offender treatment programs have largely neglected the relationship between trauma exposure in childhood and violence in adulthood. Prior evaluations have found treatment models that view violence as a result of power-control dynamics only marginally reduce reoffending. Preliminary assessments of the ACTV treatment model have demonstrated significant reductions in continued violence. Mind-body offender treatment programs may be well suited to address the neurobiophysiological effects of trauma.